Microwave and Ultrasonic‐Assisted Synthesis of Highly Functionalized Carbazoles And Dibenzofurans from Biaryl‐Triazenes Promoted by Acidic Ionic Liquid. Issue 36 (21st September 2022) - Kim, Kang Min; Sutar, Suraj M.; Kalkhambkar, Rajesh G.; Refat, Moamen S.; Alsuhaibani, Amnah Mohammed
Abstract: Brønsted acidic Ionic liquid promoted synthesis of functionalized carbazoles and dibenzofurans is reported employing biaryl‐triazene as intermediate. The shorter reaction time, diverse functional group tolerance, high yield, mild reaction condition and employment of microwave and ultrasonic assistance highlight the importance of this reaction. Approximately 80–92% of the product yield was achieved with this highly efficient green technique. Along with this, recycling and re‐use of ionic liquids are also addressed. Abstract : Highly functionalized carbazole and dibenzofuran derivatives were synthesized employing biaryl‐triazene and Brønsted acidic Ionic liquid promoter. The good yields of products were achieved within shorter reaction time by assistance of microwave irradiation and ultrasonication in ionic liquid medium.